BDNF blood levels after non-invasive brain stimulation interventions in major depressive disorder: A systematic review and meta-analysis. (February 2015) - Brunoni, André R.; Baeken, Chris; Machado-Vieira, Rodrigo; Gattaz, Wagner F.; Vanderhasselt, Marie-Anne
Abstract Objectives. To evaluate whether the antidepressant effects of novel non-invasive brain stimulation (NIBS) therapies are associated with neurotrophic effects, indexed by peripheral brain-derived neurotrophic factor (BDNF) levels. Methods. Systematic review and meta-analysis. We included trials published in PubMed/Medline from the first date available to June 2014 measuring BDNF blood levels before and after repetitive transcranial magnetic stimulation or transcranial direct current stimulation in depression. Results. Eight datasets (n = 259) were included. These studies enrolled mostly treatment-resistant depression patients, who received daily stimulation sessions on the left dorsolateral prefrontal cortex. BDNF did not increase after NIBS (Hedges' g = 0.03, 95% CI = –0.21 to 0.27), even when examining each intervention separately. Meta-regressions did not identify the influence of any clinical and demographic predictors on the outcome. Finally, Begg's funnel plot did not suggest publication bias and results were robust according to sensitivity analysis. Conclusions. Peripheral BDNF levels do not increase after NIBS in depression. Such biomarker might, therefore, not be suitable to index NIBS antidepressant response. Further trials are needed, particularly exploring non-medicated populations, performing subsequent BDNF assessments in a larger timeframe and employing more intensive NIBS treatment protocols.